Procedural actions concerning appeal in civil dispute under Kosovo legislation - Qehaja, Rrustem (Civil Procedure Review, 2017)
In this scientific paper shall be handled the description of undertaking procedural actions on the purpose of conducting procedura according to appeal against civil judgment. Appeal represents a regular legal remedy with suspensive effect in comparison to extraordinary legal remedies of attacking civil decisions which do not have suspensive effect. Therefone, a spacial attention, shall be paid to the handling of appeal in procedural terms as well actions concerning the appeal, but not to causes from which the apeal may be sumitted as a regular legal remedy dreadlines and decisions rendered by a higher degree court, and not only regarding local level how this issue is regylated by our legislation respectively by the Law on Contested Procedure (LCP) provisions, but also broader.